Psychological resilience of emergency nurses during COVID-19 epidemic in Shanghai: A qualitative study - Jiang, Jinxia; Liu, Yue; Han, Peng; Zhang, Pengjia; Shao, Haiyan; Peng, Hu; Duan, Xia (Frontiers in Public Health, 2022)
Background：In early 2022, an outbreak of Coronavirus Disease 2019 (COVID-19) occurred in Shanghai, China. The spread of the epidemic put a large amount of stress on the local healthcare system, especially emergency nurses (ENs), which may affect their well-being and performance. Enhancing the psychological resilience of ENs during COVID-19 pandemic may improve job satisfaction, retention, and public health emergency response. However, few studies have researched the perception and psychological resilience of ENs during COVID-19 pandemic. Objective: To understand the perception and psychological resilience of emergency nurses (ENs) in Shanghai, and how they cope with adversities during Coronavirus Disease 2019 (COVID-19), as well as the factors related to psychological resilience. Methods: This qualitative study was conducted using a phenomenological approach. A total of 17 ENs from a 3rd level hospital in Shanghai were selected using a method of purposive sampling. Between April and May 2022, in-depth semi-structured interviews and Colaizzi seven-step method were performed for data collection and analysis. Results: The investigation discovered three themes: risk factors, promoting factors, and motivation by altruism. Conclusions: Psychological resilience is not a stable psychological characteristic but a constantly changing process that is affected by internal and external factors. Enhancing resilience of ENs during the COVID-19 pandemic may improve work satisfaction, retention, and public health emergency response. Adequate preparation before a pandemic, reasonable arrangement, a trustworthy working atmosphere, encouragement and improvement of individual and collective strategies for nurses to cope with adversity, timely rewards, and nurse empowerment, as well as counseling and training, can be used to enhance psychological resilience of ENs.